Ultrasound diagnostics of traumatic pancreatitis at combined trauma - O. A. Alekseyechkina; E. Ya. Dubrov; D. A. Kosolapov; V. M. Abuchina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2014)
Aim of investigation. To estimate state of the pancreas in patients with combined trauma, to detect signs of traumatic pancreatitis.Material and methods. Analysis of ultrasound data in 680 patients with combined trauma was carried out. In 57 patients (42 men and 15 women, age 20 to 56 years) signs of traumatic pancreatitis of various severity were revealed at US examination. Patients were divided into two groups: the first group — 32 patients had combined trauma, including closed injury of the abdomen, the second group — 25 patients who in late terms after trauma revealed signs of acute pancreatitis on a background of developing multiorgan failure. Investigations was carried out at middle class ultrasound devices with 3,5 mHz convex probe.Results. In patients with combined trauma and closed injury of the abdomen signs of acute pancreatitis emerged, as a rule, on the 1–7 day after the moment of trauma. All forms of acute pancreatitis, including suppurative complications requiring miniinvasive intervention with US guidance: punctures and drainages in these patients were followed up at dynamic US-study. In patients of the second group signs of acute pancreatitis were revealed at 2–3 week on a background of progressing multiorgan failure.Conclusions. Traumatic pancreatitis in patients with combined trauma develops both due to direct damage of the pancreas, and as a result of developing multiorgan failure. Dynamic US-study allows to reveal in due time signs of acute pancreatitis as well as complications. Pancreatic changes may be considered as developing dysfunction of the organ at multiorgan failure.